Mathematical Problem Solving Ability in Cooperative Learning Type Student Teams Achievement Division (STAD) - Chairuddin Chairuddin; Farman Farman (JME (Journal of Mathematics Education), 2021)
This study aims to describe the mathematical problem solving ability of class IX students of SMP Negeri 1 Kolaka. The type of research used in this research is descriptive with a qualitative approach. The subjects of this study consisted of 25 students of class IXD SMP Negeri 1 Kolaka. The instruments in this study were a test of problem-solving skills and an observation sheet. The test questions for the ability to solve mathematical problems are in the form of a description test consisting of 5 questions. The observation sheet consists of teacher and student observation sheets which are arranged based on the application of STAD type cooperative learning. The data analysis technique in this study uses the Miles Huberman model which consists of data reduction, data presentation and conclusion drawing. The results showed that (1) the average mathematical problem solving ability of students taught by the STAD type cooperative learning model consisting of 25 students showed a mean value of 70, variance 82.82, and standard deviation 9.10. The average indicates that the problem-solving ability is in the good category. (2) The average percentage of teacher activity is 79.56% who are in the active category, while the average percentage of student activity is 76.67% who are in the active category. Thus, it can be concluded that STAD learning activities can facilitate the achievement of students' problem solving abilities.